REKAYASA PERANGKAT LUNAK PEMETAAN LOKASI PRAKTEK DOKTER BERBASIS WEB DI KOTA PALEMBANG - Alfian Egi Erlangga; Ari Muzakir (Jurnal Bina Komputer, 2020)
Currently, web-based applications are experiencing very rapid development to the implementation on various mobile platforms. Joint doctor practice services are becoming a trend now, given the convenience felt by the community. Usually, in one location doctors practice consists of several different specialist doctors. This is said to be the ease of service to the community. However, the increasing number of doctor's practice locations also causes many obstacles that are felt by the community, namely related to the status of the clinic location, specialist doctor information, and so on. Site mapping software engineering is a solution to overcome this. By doing engineering, we can make what the community expects. Location mapping involves several elements that can be used, for example maps and routes, distribution, and so on. This study aims to help the community to find and inform doctors about the location of doctor's practice in the city of Palembang. Software development uses prototyping methods by involving users in development. In terms of user satisfaction, this study uses usability testing by looking at several related elements such as learnability, efficiency, memorability, error, and satisfaction. The final results of this study are in the form of a system that can help the public to navigate and detailed information from the location of the doctor's clinic